100 деревянных домов: жилые и садовые домики / И. П. Кожевников, А. П. Шумов - Кожевников Игорь Петрович (Экология, 1993)
Экземпляры: (20240327) / Инвентарный номер: 23236 / Цена: 1200.00 / Сис.шифр: 38 / Авт.знак: К 58 / ББК: 38.55